2022
DOI: 10.3384/svt.2021.28.4.4366
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19-pandemins påverkan på personer med intellektuell funktionsnedsättning i Sverige

Abstract: Personer med intellektuell funktionsnedsättning har sämre levnadsvillkor än befolkningen i övrigt och är ofta beroende av andras stöd för ett gott liv. Kunskap saknas om hur deras vardagsliv, hälsa och stödinsatser påverkas av den välfärdsutmaning som covid-19-pandemin innebär. I denna artikel redovisas och diskuteras anhörigas och personals bedömningar av pandemins påverkan på personer med intellektuell funktionsnedsättning i Sverige efter sex månaders pandemi i september 2020, det vill säga efter första våge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Omställningen påverkade även personer med IF på flera sätt, bland annat eftersom dagliga verksamheter stängdes eller minskade sitt utbud. I efterhand visar erfarenheterna att många av dem som drabbades av minskad eller inställd daglig verksamhet erfor stor ensamhet och sämre välbefinnande (Socialstyrelsen, 2021;Tideman & Aspling, 2021). Mer positiva följder av stängningen har framkommit i den här studien, som den utökade IKT-användningen hos vissa personer med IF som ägde rum när IKT nyttjades för att möjliggöra daglig verksamhet på distans.…”
Section: Diskussionunclassified
“…Omställningen påverkade även personer med IF på flera sätt, bland annat eftersom dagliga verksamheter stängdes eller minskade sitt utbud. I efterhand visar erfarenheterna att många av dem som drabbades av minskad eller inställd daglig verksamhet erfor stor ensamhet och sämre välbefinnande (Socialstyrelsen, 2021;Tideman & Aspling, 2021). Mer positiva följder av stängningen har framkommit i den här studien, som den utökade IKT-användningen hos vissa personer med IF som ägde rum när IKT nyttjades för att möjliggöra daglig verksamhet på distans.…”
Section: Diskussionunclassified
“…Studies focusing on environmental aspects as either barriers or support to young people’s participation in productive occupations are emphasised [ 12 ]. In a recent scoping review about the state of the art in research concerning the transition from childhood to adulthood for people with disabilities, Tideman et al [ 12 ] stressed the need for knowledge about the long-term outcomes of support provided in school.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on environmental aspects as either barriers or support to young people’s participation in productive occupations are emphasised [ 12 ]. In a recent scoping review about the state of the art in research concerning the transition from childhood to adulthood for people with disabilities, Tideman et al [ 12 ] stressed the need for knowledge about the long-term outcomes of support provided in school. Recently, Myklebust and Båtevik [ 14 ] found that support from teacher assistants and special pedagogical support did not contribute to economic independence as adults among former students with SEN. By using a longitudinal approach, which is rare when investigating the transition from school to work among young adults with disabilities [ 12, 14 ], this present study strives to provide knowledge about establishment in productive occupations related to adult life among former students with SEN who received assistive technology support in upper secondary school.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation